Penggunaan Media Kartu Huruf Bergambar dalam Upaya Meningkatkan Kemampuan Membaca Permulaan Pada Kelompok B di TK Ihksanul Kamil - Sari Rizki; Firmawati Firmawati (Departement of Mathematics Education, 2023)
The purpose of this study was conducted to describe the increase in early reading skills in children and the activities of teachers and children in learning. The approach taken in this research is qualitative. This type of research is classroom action research. The subjects in this study were group B children, which consisted of 10 children. The technique of collecting data is through sheets of early reading skills in children and observation sheets of teacher and child activities. Children's learning outcomes after experiencing the learning process in the first cycle of meeting I, only 4 children or 40% completed, while at the second meeting, 6 children or 60% completed. In the second cycle of the 1st meeting the children who completed reached 8 children or 80%, at the 2nd meeting the children who completed 9 children or 90%. The results of observations of teacher activities at the 1st cycle I meeting obtained an average proportion of 77% and at the 2nd meeting increased to 79% and the results of observations of teacher activities at the 1st cycle II meeting obtained an average proportion of 83% and at the 2nd meeting obtained 89%, is in the good category while children's activities Children's activities during the teaching and learning process are obtained: Results of children's activities cycle I The 1st meeting obtained an average score of 71% and at the 2nd meeting it reached 76%, at the cycle II the 1st obtained the proportion of 76% and at the 2nd meeting 82%. Thus it can be concluded that the use of picture letter card media can improve children's initial reading skills, teacher and child activities in the teaching and learning process.